Dependence of magnetron characteristics on the secondary-emission yield of cold cathode - Avtomonov, N.I.; Sosnytskiy, S.V.; Vavriv, D.M. (Вопросы атомной науки и техники, 2006)
Particle simulations of mm-wavelength magnetrons with cold secondary-emission cathodes show that such important practical characteristics as the output power, efficiency, and operation current are dependent on secondaryemission properties of the cold cathode used in such magnetrons. However, in some cases, the enhancement of the magnetron characteristics can be achieved with a relatively low secondary-emission yield of the cold cathode. This opens a way for using of pure inexpensive metals for the cathode production. The interplay between the secondaryemission yield and the magnetron performance is studied to realize this approach.